Exploring the determinants of online health service usage intentions under the threat of air pollution - Xu, Xueru; Wang, Tao; Liu, Chuang; Luo, Li; Liu, Xiaofei (Frontiers in Public Health, 2024)
The rapid evolution of online health services (OHS) has significantly improved healthcare accessibility. Nonetheless, the influence of air pollution on individuals' willingness to engage with OHS remains underexplored in existing literature. This study investigates the impact of air pollution threats on OHS usage intentions, based on the frameworks of Protection Motivation Theory (PMT) and Rational Choice Theory (RCT). Utilizing cross-sectional survey data, our theoretical model was rigorously tested. Findings indicate that threat appraisal, coping appraisal, and perceived benefits positively affect the intention to use OHS, whereas perceived costs have a negative impact. Moreover, age moderates the relationship between coping appraisal and OHS usage intention. Our study extends the application of PMT and RCT within the context of OHS research, offering valuable insights into users' intentions to utilize OHS.